2017
DOI: 10.2903/sp.efsa.2017.en-1090
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation and toxicity of mineral oil hydrocarbons in rats ‐ specificity of different subclasses of a broad mixture relevant for human dietary exposures

Abstract: The purpose of this study was to investigate the fate and effects of mineral oil saturated hydrocarbons (MOSH) in female Fischer 344 rats. Animals were fed control diet or diet containing various MOSH mixtures at concentrations ranging from 40 to 4000 mg/kg feed for up to 120 days. MOSH were analysed in liver, spleen, adipose tissue and remaining carcass at different sampling times. In addition to clinical effects, liver microgranulomas, hepatic inflammation, and disruption of the immune function were the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(89 citation statements)
references
References 32 publications
(66 reference statements)
2
87
0
Order By: Relevance
“…In female F-344 rats, the strong retention in liver following exposure to paraffin waxes (e.g. LMPW) indicates the inability to efficiently metabolize absorbed n-alkanes consisting of a certain carbon number range (Smith et al 1996;Griffis et al 2010; Barp et al 2017b;Cravedi et al 2017). Even very low concentrations (0.02-0.12 ppm) of natural n-alkanes in the range of C 29 -C 33 , that were present in control feed, were found to be enriched in liver of untreated control animals (Cravedi et al 2017).…”
Section: Mosh Levels In Animal Tissuesmentioning
confidence: 99%
See 3 more Smart Citations
“…In female F-344 rats, the strong retention in liver following exposure to paraffin waxes (e.g. LMPW) indicates the inability to efficiently metabolize absorbed n-alkanes consisting of a certain carbon number range (Smith et al 1996;Griffis et al 2010; Barp et al 2017b;Cravedi et al 2017). Even very low concentrations (0.02-0.12 ppm) of natural n-alkanes in the range of C 29 -C 33 , that were present in control feed, were found to be enriched in liver of untreated control animals (Cravedi et al 2017).…”
Section: Mosh Levels In Animal Tissuesmentioning
confidence: 99%
“…Paraffinum liquidum), L-C25W: a 1:1 (w/w) mixture of L-C25 and a paraffin wax (W) (see Table 1). would be an additional factor contributing to the slow biotransformation (Barp et al 2017b;Cravedi et al 2017).…”
Section: Mosh Levels In Animal Tissuesmentioning
confidence: 99%
See 2 more Smart Citations
“…mass spectrometry). However, FID is not selective, a drawback in view of the broad patterns of unresolved peaks of unidentified components formed by mineral oils (Biedermann et al, 2009;Cravedi et al, 2017) reported Grob (2018), on-line coupled high-performance liquid chromatography (HPLC) and GC-FID) (HPLC-GC-FID)) appears to be the method of choice and its successful application was reported already in 1984 (Grob et al, 1984). The aforesaid methodology makes use of solvent effects and retention gap technology: raw food extracts or solutions of edible oils could be directly injected, which not only provided a high-performance pre-separation, but also avoided contamination during sample preparation with virtually ubiquitous mineral oil hydrocarbons.…”
Section: Methods Of Analysis In Foodmentioning
confidence: 99%